PANDANGAN PESERTA STUDY GROUP YOUCAT TERHADAP METODE KNOW, SHARE, MEET, EXPRESS DALAM KEGIATAN KATEKESE - Andita, Fransisca Putri; Wijaya, Albert I Ketut Deni (Bahasa Indonesia, 2023)
In 2021 YOUCAT Indonesia held a catechesis activity known as the Study Group. In its implementation, the Study Group uses a method known as the know, share, meet, express (KSME) method. What are the views of the Study Group participants on the KSME method? The purpose of the research is in its implementation, the Study Group uses a method called the know, share, meet, express (KSME) method. This study uses a qualitative method. To obtain research data, researchers used interview. Collecting research data is carried out both online and offline. Informants in this study are Study Group participants who have attended Study Group meetings at least 5 times. The results showed that the Study Group participants had a favorable view of the KSME method in catechesis. This is shown by the Study Group participants who being able to state the reasons why the Study Group that used the KSME method really helps participants to understand and live the Church's teachings. In addition, participants were able to mention the advantages possessed by the Study Group compared to other catechesis. Furthermore, the Study Group participants did not fail to provide suggestions on things that need to be improved so that the Study Group using the KSME method is getting better.